Anxiety, fear extinction, and threat-related amygdala reactivity in children exposed to urban trauma. Issue 4 (15th October 2022) - France, John M.; Reda, Mariam; Marusak, Hilary A.; Riser, Manessa; Wiltshire, Charis N.; Davie, William M.; Grasser, Lana Ruvolo; Wanna, Cassandra P.; Stenson, Anaïs F.; Ely, Timothy D.; Norrholm, Seth D.; Stevens, Jennifer S.; et al.
Introduction: Childhood trauma is strongly associated with fear-related psychopathology, like anxiety and posttraumatic stress disorder (PTSD). Atypical fear extinction and neural responses to social threat (i.e., negative emotional faces) may serve as intermediate phenotypes preceding the emergence of fear-related psychopathology during childhood and adolescence. However, few studies have examined associations among these phenotypes in trauma-exposed youth. Methods: 29 9-year-old children with high rates of trauma exposure (Mdn = 4, min = 0, max= 14 total events) completed a fear-potentiated startle paradigm assessing fear conditioning and extinction and an emotional faces functional magnetic resonance imaging (fMRI) task assessing neural responses to fearful and neutral faces. Results: Overall amygdala response was positively associated with anxiety (peak coordinates: x = −30, y = −6, z = −24; Z = 3.54; pFWEcorrected = 0.011; k = 24 voxels) and fear-potentiated startle during early extinction (peak coordinates x = 28, y = −6, z = −18; Z = 3.50; pFWEcorrected = 0.012; k = 19 voxels). Across the session, amygdala reactivity to fearful faces increased (F(1, 29) = 4.427, p = .044) and was positively associated with fear-potentiated startle during early extinction (r = .56, p = .002). Conclusions: We found a positive association between increasing amygdala response to threatening faces and fear load, that is, heightened fear-potentiated startle during early extinction, in trauma-exposed children. These fear-based intermediate phenotypes may share underlying amygdala circuits, such that hyperactivity may represent an early marker of anxiety risk in trauma-exposed youth.